Satellite quantification of oil and natural gas methane emissions in the US and Canada including contributions from individual basins - L. Shen; L. Shen; L. Shen; R. Gautam; M. Omara; D. Zavala-Araiza; D. Zavala-Araiza; J. D. Maasakkers; T. R. Scarpelli; A. Lorente; D. Lyon; J. Sheng; et al. (Atmospheric Chemistry and Physics, 2022)
We use satellite methane observations from the Tropospheric Monitoring Instrument (TROPOMI), for May 2018 to February 2020, to quantify methane emissions from individual oil and natural gas (O/G<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="25pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="de44095387c3ea4f1955a8c63a05620f"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-22-11203-2022-ie00001.svg" width="25pt" height="14pt" src="acp-22-11203-2022-ie00001.png"/></svg:svg>) basins in the US and Canada using a high-resolution (∼25 km) atmospheric inverse analysis. Our satellite-derived emission estimates show good consistency with in situ field measurements (R=0.96) in 14 O/G<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="25pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="08bad6efd69ceabf5adda748d2163fa4"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-22-11203-2022-ie00002.svg" width="25pt" height="14pt" src="acp-22-11203-2022-ie00002.png"/></svg:svg> basins distributed across the US and Canada. Aggregating our results to the national scale, we obtain O/G<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="25pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="351b0d2fecc903a8c24a76cb0c1c525d"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-22-11203-2022-ie00003.svg" width="25pt" height="14pt" src="acp-22-11203-2022-ie00003.png"/></svg:svg>-related methane emission estimates of 12.6±2.1 Tg a−1 for the US and 2.2±0.6 Tg a−1 for Canada, 80 % and 40 %, respectively, higher than the national inventories reported to the United Nations. About 70 % of the discrepancy in the US Environmental Protection Agency (EPA) inventory can be attributed to five O/G<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="25pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="d4c5f68eb7cb1e8a0de33a61761f053a"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-22-11203-2022-ie00004.svg" width="25pt" height="14pt" src="acp-22-11203-2022-ie00004.png"/></svg:svg> basins, the Permian, Haynesville, Anadarko, Eagle Ford, and Barnett basins, which in total account for 40 % of US emissions. We show more generally that our TROPOMI inversion framework can quantify methane emissions exceeding 0.2–0.5 Tg a−1 from individual O/G<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="25pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="a5ffabfc5f518014745f14484714a544"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-22-11203-2022-ie00005.svg" width="25pt" height="14pt" src="acp-22-11203-2022-ie00005.png"/></svg:svg> basins, thus providing an effective tool for monitoring methane emissions from large O/G<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="25pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="6e0ae023bb0fafc236eda341897f0034"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-22-11203-2022-ie00006.svg" width="25pt" height="14pt" src="acp-22-11203-2022-ie00006.png"/></svg:svg> basins globally.